Immunomodulatory effect of glucan on the response to experimental antirabies vaccination - Tino, Milene S. [UNIFESP] (1993)
The objective of lhe present study was to determine the stimulatory response to antirabies vaccination promoted by glucan in mice. Glucan increased both resistance to infection and antibody titres and this effect was more evident when glucan was used at dose of 0.5 mg, administered intraperitoneally before, during and after immunization and when the challenge virus was applied to the foot-pad.